2010
DOI: 10.4236/abb.2010.15054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid regeneration of stable transformants in cultures of potato by improving factors influencing Agrobacterium-mediated transformation

Abstract: An efficient and rapid Agrobacterium tumefaciens-mediated transformation protocol was developed to generate activation-tagged mutant lines with the aim of large-scale functional analysis of the potato genome. The explants were inoculated with an Agrobacterium strain harboring the binary plasmid pSKI074 containing four CaMV 35S enhancers in the T-DNA region which activates the downstream genes in the host plant after its integration. Various parameters investigated to increase transformation efficiency were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…So we tried another infection time (5min) 3-days co-cultivation and some explants survive and then transferred for cultivation MS media. This agree with [17] who used 5-min infection into two potato cultivars from Bangladesh (cardinal and heera), [31], from Molecular Plant Pathology Laboratory in USA, who worked on two Serbian potato cultivars (Dragaevka and Jelica) and [32] To sum up, the difference in infection periods of explants with Agrobacterium could be due to firstly, used different cultivars which could be differ in their sensitivity to infection with bacteria. Secondly it may be due to use different explants for infection (node, internode or leaf segment), finally it could be due to different environmental conditions which completely different differ from the environmental conditions in Egypt.In this study, we selectednodal explants for transformation because [23] proved that the nodal explants are much more resistant during manipulation and more amenable to in vitro conditions.…”
Section: Discussionsupporting
confidence: 72%
“…So we tried another infection time (5min) 3-days co-cultivation and some explants survive and then transferred for cultivation MS media. This agree with [17] who used 5-min infection into two potato cultivars from Bangladesh (cardinal and heera), [31], from Molecular Plant Pathology Laboratory in USA, who worked on two Serbian potato cultivars (Dragaevka and Jelica) and [32] To sum up, the difference in infection periods of explants with Agrobacterium could be due to firstly, used different cultivars which could be differ in their sensitivity to infection with bacteria. Secondly it may be due to use different explants for infection (node, internode or leaf segment), finally it could be due to different environmental conditions which completely different differ from the environmental conditions in Egypt.In this study, we selectednodal explants for transformation because [23] proved that the nodal explants are much more resistant during manipulation and more amenable to in vitro conditions.…”
Section: Discussionsupporting
confidence: 72%
“…The research was carried out by Chakravarty & Pruski (2010) showed that OD 600 = 0.2 could improve significantly the average efficiency transformation of Agrobacterium rhizogenes on potato.…”
Section: Induction Of Hairy Roots By a Rhizogenesmentioning
confidence: 99%
“…These data are in agreement with Yin et al (2005), they showed that the frequency of Agrobacte-rium-mediated transformation ranged from 0.8 to 10% and was influenced by bacteria cell density. Chakravarty and Wang-Pruski (2010) reported that from various parameters investigated to increase transformation efficiency was concentration of bacterial cultures which used for transformation. Different concentration of bacterial suspension (OD600 0.2-0.6) were used.…”
Section: Effect Of Agrobacterium Concentrationmentioning
confidence: 99%